2019
DOI: 10.1029/2018gl080555
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Content in the Earth's Outer Core

Abstract: Using first principles molecular dynamic simulations, we explore the effects of nitrogen (N) on the density and sound velocity of liquid iron and evaluate its potential as a light element in the Earth's outer core. Our results suggest that Fe‐N melt cannot simultaneously explain the density and seismic velocity of the Earth's outer core. Although ~2.0 wt.% N can explain the bulk sound velocity of the outer core, such N content only lowers the density of liquid Fe by ~3%. Matching both the velocity and density … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 93 publications
0
11
0
Order By: Relevance
“…Minobe et al (2015) however discussed that the maximum nitrogen content in the core should be about 1 wt% from its abundance in CI chondrites. From the first principles calculations of the sound velocity and density of the Fe-N liquids, Bajgain et al (2018) concluded that the nitrogen content in the outer core would be less than 2 wt%. As such, the estimated nitrogen content in the core is not high and there must be some other light elements in there.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Minobe et al (2015) however discussed that the maximum nitrogen content in the core should be about 1 wt% from its abundance in CI chondrites. From the first principles calculations of the sound velocity and density of the Fe-N liquids, Bajgain et al (2018) concluded that the nitrogen content in the outer core would be less than 2 wt%. As such, the estimated nitrogen content in the core is not high and there must be some other light elements in there.…”
Section: Discussionmentioning
confidence: 99%
“…As a major volatile element in the atmosphere, the presence of water/hydrogen in the core and its consequences have been discussed (e.g., Okuchi 1998;Nomura et al 2014) as well as its circulation in the mantle (e.g., Komabayashi 2006). On the other hand, nitrogen which is another major component of the atmosphere has received less attention and its circulation and storage in the deep Earth were less studied (Mikhail et al 2017;Minobe et al 2015;Litasov et al 2017;Bajgain et al 2018) despite of its abundance in meteorite from thousand ppm (chondrites) to 1 wt% (iron meteorites) (see Litasov et al (2017) and reference therein). In order to discuss the storage of nitrogen in the core, phase relations in the system Fe-N should first be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Aside from a limited number of experimental (for a review, see Li & Fei, ) and computational studies (e.g., Alfè et al, ; Badro et al, ; Li, Vočadlo, Alfè, et al, ; Li, Vočadlo, & Brodholt, ), Criterion (iv) remains poorly constrained due to experimental challenges and inherent nonuniqueness of the problem. Nevertheless, the geophysically most interesting and discussed alloy components for the Earth's core are H, C, N, O, Mg, S, Si, and Ni (Badro et al, ; Bajgain et al, ; Dalou et al, ; Li, Vočadlo, Alfè, et al, ; McDonough, ; Takafuji et al, ). In addition to the alloying elements relevant for core density that we consider here, there are also a number of geochemically significant—less abundant—moderately or slightly siderophile elements, such as V, Cr, Co, or W, which are important tracers for core formation conditions (e.g., Fischer et al, ; Rubie et al, ) and timing (e.g., Kleine et al, ) as well as heat‐producing lithophile elements, such as K and U (e.g., Blanchard et al, ), which play an important role in the thermal evolution of the Earth (e.g., Davies, ).…”
Section: Introductionmentioning
confidence: 99%
“…The N solubility in the core condition is the order of ∼10 wt.% (Speelmanns et al, 2018). In contrast, geophysical constraints limit the N abundance in the core to be ≪ 2.0 wt.% (Bajgain et al, 2019) and modeling of Earth's accretion and volatile partitioning has estimated the core N abundance to be ∼10-100 ppm (Sakuraba et al, 2021), both of which are much smaller than the saturation level. Second, the N exchange at the core-mantle boundary (CMB) would be insufficient to supply N from the core to explain the modern mantle N abundance.…”
Section: Model Uncertainties and Limitationmentioning
confidence: 99%